Mobile cloud computing & mobile's battery efficiency approaches: A review - Ali, Mushtaq; Jasni, Mohamad Zain; Mohamad Fadli, Zolkipli; Badshah, Gran (JATIT, 2015)
Today, millions of users worldwide experience pervasive email and Web access through IPhones, Black Berries, Windows Mobile, and other mobile devices (Laptops, PDAs). After information at the fingertip, energy efficiency of these devices is paramount which makes the devices first choice of communication for the new generation. On the other hand, Mobile Devices, especially smartphones has limited resources such as, storage, network bandwidth, processor’s performance and battery life. Moreover multiple sensors and wireless interfaces drain battery swiftly, thus reducing the operational time. Therefore, extending battery life of these devices has become of crucial research importance at hardware and software levels, both alike. This paper provide an overview of the software side by summarizing the background, techniques of battery augmentation, and on-going research on computational offloading to remote servers (Cloud); sending heavy computation to remote servers and receiving the result back on mobile screen. At the end, summary of the previous research work on computational offloading discussed with a critical analysis. Moreover, suggestions and opinions related to energy efficiency of SIDs given, based on the comparative studies.